If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2544c + -967b + -123c = x Reorder the terms: -967b + 2544c + -123c = x Combine like terms: 2544c + -123c = 2421c -967b + 2421c = x Solving -967b + 2421c = x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2421c' to each side of the equation. -967b + 2421c + -2421c = -2421c + x Combine like terms: 2421c + -2421c = 0 -967b + 0 = -2421c + x -967b = -2421c + x Divide each side by '-967'. b = 2.503619442c + -0.001034126163x Simplifying b = 2.503619442c + -0.001034126163x
| -6(5-2x)=17 | | -w-3/5=2w | | 10y+4=2(5y+8)-12 | | 15=4y+11-2y | | -4x+24=-4 | | 9*2=18*1 | | -8=a+a+6 | | 9x-13x=28 | | 14x+6= | | 5y(y-9)=0 | | 17-5k=2 | | 5=-3a-7 | | 39-n=5n-3(8+5n) | | 2y-10=18 | | 4(18-1)=2(18+7) | | 7-6x=4y | | 4x-2x=3+7 | | -18=2m-68 | | 86=5(x+8)+6 | | 4(36-1)=2(36+7) | | 91=2x+7x+1 | | xb+z=m-2x | | 4(5-1)=2(5+7) | | 15-3.2(6.8125)=-6.8 | | X-(4x-7)=5x-(x+2) | | 4(x-2)=-2(3-3x) | | 5x-6-7=x+6+x | | (-4x+6)+(6x-10)=0 | | 4(9-1)=2(9+7) | | -(k-12)=48 | | 4(9-1)=2(x+7) | | bx+z=m-2x |